Analysis Of The Effect Of Key Opinion Leaders On Purchase Intention For Household Products On The Instagram Account @Ulvilolyamanda (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
The utilization of Key Opinion Leaders (KOLs) on Instagram social media has become a popular marketing strategy. This research aims to examine and analyze the partial and simultaneous influence of three main source attributes—Trustworthiness, Attractiveness, and Expertise—on the Purchase Intention of household product consumers among followers of the @ulvilolyamanda Instagram account. The study employs a quantitative approach with a survey method. Data was processed using Multiple Linear Regression analysis techniques. The research sample consisted of active followers of the @ulvilolyamanda Instagram account who had been exposed to household product promotional content and were at least 18 years old. The analysis results indicate that simultaneously, Trustworthiness, Attractiveness, and Expertise significantly influence Purchase Intention. However, partially, only Trustworthiness and Expertise have a positive and significant influence on Purchase Intention. The Expertise variable was identified as the most dominant predictor (β=0.444). Conversely, Attractiveness did not have a significant partial influence (Sig.=0.252) on Purchase Intention. Descriptively, all KOL attribute variables were perceived as very good by the respondents. The Purchase Intention of household product consumers is dominated by cognitive factors (expertise and honesty) rather than affective factors (visual attractiveness). The implication of this finding is that household product brands should prioritize content that highlights the KOL's technical expertise in product usage and the honesty of reviews to maximize the potential conversion of consumer purchase intention.